Projeto social na empresa júnior: INCOP da Unesp Bauru - Goya, Julia Yuri Landim [UNESP]; Orfão, Beatriz Mayumi Kayo [UNESP]; Bortolussi, Leonardo Martins [UNESP]; Wakamatsu, Lucas [UNESP]; Tagliatela, Luiza Boarato [UNESP]; Rodrigues, Osmar Vicente [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Design Junior is a junior enterprise of design from UNESP Bauru. Our company works half period, in a way that all students may join academic life and working in the company. The Design Junior works mainly with graphic projects, and has as its focus creation of materials for companies, organizations, events like meetings, forums, conferences, lectures, talks, festivals and workshops. The Junior Company prefers to choose social projects. We believe that it’s not necessary to belong to a specific social class or possesses resources to have a quality design. Among them, we will present “INCOP”.

A Design Júnior é a empresa júnior de design da UNESP. A empresa funciona meio período, de maneira com que todos os integrantes possam adequar o trabalho à vida acadêmica. Entre os projetos que desenvolvemos consta a criação de projetos gráficos, e como principal público pequenas empresas e projetos da universidade. A Empresa Júnior preza e não cobra por projetos de cunho social, acreditamos que não é necessário pertencer a uma classe social específica ou possuir recursos privilegiados para se ter acesso a um design de qualidade. Entre eles, traremos em foco a ”INCOP”, incubadora de cooperativas populares da UNESP de Bauru.
Keywords: Design; Social; Leaning; Design; Social; Aprendizagem